2007
DOI: 10.1111/j.1939-165x.2007.tb00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of myelin basic protein in the cerebrospinal fluid of dogs with degenerative myelopathy

Abstract: The MBP ELISA has potential as a supplemental test of CSF to diagnose demyelinating disorders in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…This assay is intended for the measurement of human MBP in CSF, and contains a goat antihuman MBP antibody. Previously published data 18 have supported the detection of canine MBP by the goat antihuman MBP antibody. In-house validation of the assay in the study reported here consisted of intra-and interassay variability, dilutional parallelism, and spiking recovery.…”
Section: Sample Collection and Testingmentioning
confidence: 67%
See 1 more Smart Citation
“…This assay is intended for the measurement of human MBP in CSF, and contains a goat antihuman MBP antibody. Previously published data 18 have supported the detection of canine MBP by the goat antihuman MBP antibody. In-house validation of the assay in the study reported here consisted of intra-and interassay variability, dilutional parallelism, and spiking recovery.…”
Section: Sample Collection and Testingmentioning
confidence: 67%
“…30 Dogs with degenerative myelopathy and control dogs did not have significant differences in cisternal CSF MBP concentration, although dogs with degenerative myelopathy did have higher CSF MBP concentration compared with controls when samples from the lumbar cistern were analyzed. 18 Sample size and the site of CSF collection may have contributed to the lack of statistical significance for some comparisons. Differences in breed distribution and chondrodystrophoid status between the control and affected populations also may have influenced measured associations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pNF can be readily detected in the serum and CSF (65). A recent study also examined this neurofilament in dogs with spinal cold injury (SCI) following intervertebral disc disease (43). The authors found that mean pNF-H serum levels were significantly higher in dogs with no pain perception than in those with intact pain perception.…”
Section: Introductionmentioning
confidence: 96%
“…However, some dogs with SCI did not have high pNF-H levels between day one and day three after injury. Furthermore, dogs with no pain perception, which did not regain ambulation following surgery, had significantly higher pNF-H levels in comparison to those that regained ambulation following surgery (43). Hayakawa et al (25) found the plasma pNF-H levels to be detectable within 96 h in humans following SCI and to remain elevated for up to 21 days.…”
Section: Introductionmentioning
confidence: 99%
“…Other protein types that have been investigated for their diagnostic potential include myelin basic protein, associated with degenerative myelopathy (Oji et al, 2007), and C-reactive protein (CRP) which may help distinguishing bacterial and viral meningoencephalitis (Fishman, 1992).…”
Section: Total Protein Concentrationmentioning
confidence: 99%